How Does a Walker Pass Between Two People Standing in Different Configurations? Influence of Personal Space on Aperture Passing Methods - Tomono, Takayuki; Makino, Ryosaku; Furuyama, Nobuhiro; Mishima, Hiroyuki (Frontiers in Psychology, 2019)
Most studies on aperture passability focus on aperture passing involving nonhuman physical objects. In this study, we examined experimentally how participants pass between two box-shaped frames and between the same frames, each with a human confederate in it, facing various directions. Seven configuration conditions were set up, six of which differed in terms of the human confederates’ sets of directions in the two frames: face-to-face, back-to-back, facing toward or away from the participants, facing leftward or rightward from the participants’ perspective, and the empty frames condition without human confederates. There were seven aperture-width conditions—50, 55, 60, 65, 70, 75, and 80 cm—and participants walked at their normal speed through the apertures. We found that the participants’ shoulder rotation angle in the face-to-face condition was significantly greater than that in the empty frames condition. Further, the participants preferred to rotate their shoulders counterclockwise when our confederates in the aperture faced leftward, and clockwise, when they faced rightward. These results suggest that people change their passing-through methods by considering the social nature of the aperture as well as its width.